The Comparıson Of Two Dıfferent Method Used In The Measurement Of Sella Turcıca Area - İsmail Ceylan; Abubekir Harorlı (Galenos Yayinevi, 1991)
The present study was carried out in order to compare two different methods used in the measurement of the area of the sella turcica in which the Glandula Hypophisia is located. Two investigators separately measured the area of the sella turcica on 30 cephalometric head films, 16 males and 14 females, using both planimeter and squared millimeter paper. Two weeks after, the investigators repeated the tracings and measurements. The first and second measurements were compared and no statistically significant differences were found. While the differences between the planimetric measurements of two investigators and also between the squared millimeter paper measurements of them were statistically insignificant, the significant differences were found between the two methods.